2022
DOI: 10.3389/fcimb.2022.799668
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the P21 Gene of Trypanosoma cruzi Provides Evidence of P21 as a Mediator in the Control of Epimastigote and Intracellular Amastigote Replication

Abstract: P21 is an immunomodulatory protein expressed throughout the life cycle of Trypanosoma cruzi, the etiologic agent of Chagas disease. In vitro and in vivo studies have shown that P21 plays an important role in the invasion of mammalian host cells and establishment of infection in a murine model. P21 functions as a signal transducer, triggering intracellular cascades in host cells and resulting in the remodeling of the actin cytoskeleton and parasite internalization. Furthermore, in vivo studies have shown that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It has also been observed that this process has a direct impact on the cell cycle. It caused the cessation of the cell cycle at the G1 phase which eventually slowed cell division and growth rate of epimastigotes (Teixeira et al 2022).…”
Section: Toxoplasmosis and Chagas Diseasementioning
confidence: 99%
“…It has also been observed that this process has a direct impact on the cell cycle. It caused the cessation of the cell cycle at the G1 phase which eventually slowed cell division and growth rate of epimastigotes (Teixeira et al 2022).…”
Section: Toxoplasmosis and Chagas Diseasementioning
confidence: 99%
“…Tissue culture-derived trypomastigotes of T. cruzi (TCT, Y strain) were kept in VERO cells in RPMI 1640 medium supplemented with penicillin and streptomycin and 2% FBS at 37°C and 5% CO 2 (43).…”
Section: Cell Culture and Parasite Maintenancementioning
confidence: 99%
“…Purification of recombinant P21 protein (GenBank: EU004210.1) was carried out as previously described (43,62).…”
Section: Rp21 Purificationmentioning
confidence: 99%
See 2 more Smart Citations